A Visualized Isothermal Amplification Method for Rapid and Specific Detection of Emetic and Non-emetic Bacillus cereus in Dairy Products - Wang, Lei; Yang, Huansen; Wang, Kun; Yang, Haitao; Zhao, Mengdi; Shang, Yuping; Wang, Fang; Dong, Jingquan; Zhao, Weiguo; Li, Li; Liang, Wei; Wang, Yan (Frontiers in Microbiology, 2022)
Abstract Bacillus cereus is widely distributed in foods, especially in dairy products. It can lead to diarrhea (non-emetic Bacillus cereus) and emesis (emetic Bacillus cereus). Diarrhea is usually mild, however, emesis may lead to acute encephalopathy and even death. To develop rapid and sensitive detection methods for Bacillus cereus in foods, specific primers targeting to the gyrase B and cereulide synthetase genes were designed and screened using recombinase polymerase amplification (RPA). Probes and base substitutions were introduced to improve the specificity and eliminate the primer-dependent artifacts. The 5’ end of reverse primers and probes were modiﬁed with biotin and fluorescein isothiocyanate to make the RPA products be detected on a lateral flow strip (LFS). The developed RPA-LFS systems allowed detection within 20 min under 37°C with no cross-reaction with other foodborne pathogens. The limit of detection was both 104 copies/mL or 102 CFU/mL in pure cultures and milk. The established methods were also evaluated in cream by comparing with standard culturing method and obtained consistent results. The present study develops specific, rapid and sensitive RPA-LFS systems to identify Bacillus cereus in dairy products and distinguish non-emetic and emetic Bacillus cereus for the first time and broadens the diagnosis on site.